ON A NEW SPECIES OF DOLICHOGENIDEA VIERECK (HYMENOPTERA : BRACONIDAE) FROM INDIA - BHOJE, P. M.; SATHE, T. V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
A female braconid, Dolichogenidea sushillisp. nov. have been described for the first time from India as 3.82 mm long excluding ovipositor, head 0.55 mm long, thorax 1.35 mm long, forewing 2.97 mm long, hindwing 2.10 mm long, hind leg 3 15 mm long abdomen 1.73 mm long. Flagellar formula : 2 L/W=0.2, 8 L/W=0.1, 14L/W=0.1. L. 214=14. W 2/14=0.1